Skills of the "unskilled" : work and mobility among Mexican migrants - Hagan, Jacqueline Maria, 1954-; Hernández-León, Rubén; Demonsant, Jean-Luc (University of California Press, 2015)
"Most labor and migration studies classify migrants with limited formal education or credentials as 'unskilled.' Despite the value of their work experiences and the substantial technical and interpersonal skills developed throughout their lives, their labor market contributions are often overlooked and their mobility pathways poorly understood. Skills of the Unskilled reports the findings of a five-year study that draws on binational research including interviews with 320 Mexican migrants and return migrants in North Carolina and Guanajuato, Mexico. The authors uncover their lifelong human capital and identify mobility pathways associated with the acquisition and transfer of skills across the migratory circuit, including reskilling, occupational mobility, job jumping, and entrepreneurship."--Provided by publisher